REVISITING THE PROJECT RISKS CLASSIFICATION WITH THE COLLABORATION OF STRATEGIC STAKEHOLDERS: REVISITING THE PROJECT RISKS CLASSIFICATION WITH THE COLLABORATION OF STRATEGIC STAKEHOLDERS - Fernandes Bella, Ricardo Luiz; Negreiros, Ruan Lucas Fernandes de; Brito Alves Lima, Gilson; Huamanchumo Gutierrez, Ruben (Brazilian Journal of Production Engineering, 2020)
This article is a version of a paper previously published in the National Congress of Management Excellence (CNEG) which purpose is to illustrate how the project risk classification can be performed in a collaborative and comprehensive manner through the application of structured questionnaires to assess the probability and impact of the risks. For this, the methodology used was divided into four stages: (1) presentation of the project management tools and techniques that can be combined to assist in the classification of risks (they are: the assessment of probability and impact; the probability matrix and impact, and expert opinion); (2) presentation of the collaborative project risk classification process; (3) presentation of the structure of the probability and impact assessment questionnaire; and, (4) presentation of the data treatment method for the classification of risks. As a contribution, the study brings a methodological proposal for the classification of project risks that allows the project team to incorporate strategic stakeholders into the project risk management process and that can be applied to any type and size of the project.
Keywords: Project management; risk classification; collaborative work